PENGARUH METODE TANYA JAWAB DENGAN MENGGUNAKAN MEDIA AUDIO-VISUAL TERHADAP MINAT BELAJAR - Malia, Likha (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2022)
The low interest in student learning in the subjects of moral aqidah, teachers who use the lecture method results in low student interest in learning. In this case the teacher of the subject of aqidah morality changes the learning strategy with the question and answer method using audio-visual media. The purpose of this study was to determine whether there was an effect of the question and answer method using audio-visual media on students' interest in learning in the subjects of aqidah morality. The research method is quantitative multiple linear regression. The results of this study conclude that the question and answer method variable (X1) partially has a significant influence on the dependent variable, namely interest in learning (Y) in the subjects of aqidah morality class V MI Manbail Futuh Jenu Tuban as evidenced by the value of t count (7.333) t table (2.026) and sig (0.000) or 0.05 then Ho is rejected and H1 is accepted. As for the audio-visual media variable (X2), the partial test is not significant and there is no effect on the dependent variable, namely student learning interest (Y) in the subject of aqidah morality class V MI Manbail Futuh Jenu Tuban as evidenced by the value of t count (0.056) t table (2.026) and sig value (0.955) 5% or 0.05, then for the audio-visual media variable (X2) Ho is accepted and H1 is rejected. As for the simultaneous test (f test) independent variable question and answer method using audio-visual media there is a significant influence on student learning interest as evidenced by the value of f arithmetic (45.266) f table (3.23) and sig value (0.000) 0.05 then Ho is rejected and H1 is accepted.